Sustainable intensification of potato zero-tillage using rice straw mulch Optimizing agronomic practices in eastern India - Kakraliya, S.; Ramírez, D.; Ninanya, J.; Silva Díaz, C.; Kumar, B.; Singh, S.; Choudhary, A.; Gatto, M.; Kreuze, Jan F. (Elsevier, 2025)
Potato production under zero-tillage with rice straw mulch (PZTM) is an innovative and sustainable approach that enhances crop productivity, profitability, and resource-use efficiency while mitigating greenhouse gas emissions. This study aimed to optimize mulching thickness, plant spacing, fertilization strategies, and potato varieties under PZTM conditions during the Rabi seasons of 2021–22 and 2022–23 in Patna, Bihar, India. A randomized complete block design was implemented, consisting of four trials and 12 treatments, replicated three times, to assess the effects of varying fertilizer sources, mulch thickness, plant spacing, and potato varieties. Results demonstrated that integrating organic and inorganic fertilizers yielded the highest agronomic and economic benefits, achieving a 60 % yield increase over the control. Environmental assessments revealed that treatments incorporating organic inputs significantly reduced C footprints compared to inorganic-only systems. Among the tested potato varieties, Kufri Khyati, Kufri Uday, Kufri Jyoti, Kufri Thar-2, and Kufri Pukhraj exhibited superior performance, yielding 35–38 t ha−1, making them highly suitable for PZTM. Optimal mulch thickness (14–18 t ha−1) and plant spacing (50 × 20 cm) enhanced yields and profitability while minimizing nonmarketable tubers and greening. These findings underscore the potential of PZTM as a sustainable potato production system within rice-potato cropping systems. Adopting key PZTM agronomic practices—integrated fertilization, optimized mulching, and strategic spacing—can help farmers achieve higher yields, improved economic returns, and environmental sustainability. This study provides valuable insights for policymakers and farmers seeking to implement sustainable intensification strategies in potato cultivation.